Introduction: Emergency obstetrical care as a maternal death reduction strategy - Távara Orozco, Luis (2015)
Since the launch in Nairobi Safe Motherhood Initiative in 1987, the emphasis was on the world to a series of interventions in order to reduce maternal deaths. It's been just over 20 years and still these deaths have not declined, particularly in third world countries. Within the multiple that is supported for maternal mortality in the end the death occurs because a woman's pregnancy complication, which if severe can result in death is inserted. From there then that if the woman is taken care of in this situation by qualified personnel and in a suitable environment, it can overcome the occurrence of this complication and attend a successful outcome.